Akad Qardh Hasan Dalam Perspektif Maqashid Syariah - Wahab, Abdul (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
Qardh as a contract is a type of financing without any reward. Maqashid Sharia is the goal of establishing sharia which is directed towards maslahah. The application of qordh must be based on the basis of maqashid sharia, in order to achieve mutual maslahah. The relationship between qordh and maqashid sharia is the focus of this research. This research belongs to the type of qualitative research with technical literature, namely reading books and relevant research results, the books read can be in the form of textbooks, encyclopedias and dictionaries. The analysis is carried out with a deductive mindset, which is based on general facts and then researched and finally put forward a specific problem solving, with qualitative descriptive techniques in order to find knowledge of the research subject at a certain time. Qardh in the context of maqashid sharia is included in the realm of hifdzul mal (guarding property) from damage, in this case keeping Muslim assets in the hands of moneylenders. So that the property of a Muslim can be safe and not burdened with bloated bills. This is because in qardh a Muslim who becomes a customer only needs to return what he borrowed. So that the maslahah which is the goal of maqashid is achievedÂ Keywords: Qardh, Maqashid Syariah,